Ultra-low interest rates, overinvestment, and growth in emerging East Asia - Gunther Schnabl (Asian Development Bank Institute (ADBI), 2017)
The paper explores business cycles and growth dynamics in emerging East Asia within an ultra-low interest rate environment from the perspective of the monetary overinvestment theories of Mises and Hayek. It argues that, given a low interest rate environment in the large industrialized countries, the likelihood of overinvestment and therefore a crisis in emerging East Asia has increased independently from the exchange rate regime. Overinvestment can take the form of unsustainable booms on stock and real estate markets (as in Southeast Asia prior to the Asian crisis) or the misallocation of funds due to subsidized state-directed capital allocation (as is currently occurring in the People's Republic of China). If further credit expansion counteracts a crisis triggered by a preceding overinvestment boom, it paralyzes growth in the long term, as Japan experienced.
Keywords: E52; E58; F31; 330; Economics; Finance sector development; China; People's Republic of; Indonesia; Japan; Korea; Republic of; Malaysia; Philippines; Thailand